The Effect of Antenatal Education on Expectant Fathers' Attitudes toward Breastfeeding and Attachment to the Fetus - Calliope Dagla; Evangelia Antoniou; Antigoni Sarantaki; Maria Iliadou; Irina Mrvoljak-Theodoropoulou; Ewa Andersson; Maria Dagla (MDPI AG, 2023)
Background: This study explores the effect of antenatal education on fathers' attitudes toward: (i) breastfeeding and (ii) attachment to the fetus. A secondary aim is to explore the relationship of fathers' demographic and the psycho-emotional characteristics that come with breastfeeding and attachment. Methods: This is a longitudinal study involving a group of 216 Greek expectant fathers who participated with their partners in an antenatal educational program performed by midwives in Athens, Greece (September 2020-November 2021). The Iowa Infant Feeding Attitudes Scale (IIFAS) and Paternal Antenatal Attachment Scale (PAAS) were administered at two time points: (a) 24th-28th gestation week and (b) 34th-38th gestation week. The T-test and Univariate Analyses of Variance (ANOVA) were performed. Results: The expectant fathers' scores show that breastfeeding intention/exclusivity and prenatal attachment to the fetus were higher after their participation in the antenatal education program, but the difference was not statistically insignificant. Expectant fathers with a cohabitation agreement (p = 0.026), who felt very much supported by their partners (p = 0.001) and had no relationship difficulties with their partners (p < 0.001), as well as those who reported being very happy during pregnancy (p < 0.001), showed greater paternal antenatal attachment to the fetus. Conclusions: Although the difference was statistically insignificant, antenatal education appears to have an impact on paternal breastfeeding attitudes and antenatal attachment to the fetus. Additionally, several paternal characteristics were associated with greater antenatal attachment. Future research should be directed toward the investigation of additional factors that impact antenatal-paternal attachment and breastfeeding attitudes so that effective education programs can be designed.